Lutetium-containing aluminum-magnesium alloy and ingot homogenization treatment method thereof

CN122879566APending Publication Date: 2026-10-09SOUTHWEST UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610993245.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

但现有轻稀土改性体系存在显著技术短板:一是镧、铈轻稀土与铝镁基体的结合稳定性较弱,高温服役条件下易出现析出相粗化、组织松弛现象,合金高温力学性能与热稳定性衰减明显,无法适配高温、交变载荷等严苛工况;二是现有稀土铝镁合金未建立Si、Fe、Cu杂质元素的比例约束机制,杂质无序富集易形成针状、块状脆性金属间化合物,割裂合金基体,显著降低合金塑性与断裂韧性;三是传统热处理工艺参数固化,未根据铸锭尺寸、合金成分差异化适配,薄锭易过烧、厚锭均质不彻底,工艺适配性差,批量产品性能一致性难以保障

Benefits of technology

(1)本发明构建了高精度可控的含镥铝镁合金组分体系,采用镥稀土元素改性,并配套建立Si、Fe、Cu三元杂质比例约束机制,限定Si质量占比小于Fe质量占比、三者总含量可控的配比规则,从成分源头抑制脆性化合物生成,实现基体晶界净化与组织细化,突破了传统轻稀土改性铝镁合金热稳定性差、杂质缺陷多的技术瓶颈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879566A_ABST
    Figure CN122879566A_ABST
Patent Text Reader

Abstract

The application discloses a kind of containing Lutetium aluminum magnesium alloy and its ingot homogenization processing method, belong to aluminum alloy preparation technical field, alloy limit Mg, Mn, Cr, Lu etc. Precise component interval, establish Si<Fe and Si, Fe, Cu total content controllable impurity ratio constraint system;By lutetium element modification, form dispersed superfine Al3Lu strengthening phase in alloy matrix, eliminate continuous network Mg2Al3 brittle phase.The application differentiates using double mode homogenization process, thin specification ingot adopts platform constant temperature process, medium thickness and large thickness ingot adopts two-stage step temperature control process, match the heat diffusion characteristics of different ingot size.The application effectively solves the defects that thin ingot is easy to overburn in traditional process, thick ingot is not completely homogeneous, the alloy prepared is pure and uniform, residual stress is low, low-temperature toughness and corrosion resistance are excellent, and process adaptability is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aluminum-magnesium alloy material preparation technology, specifically relating to a lutetium-containing aluminum-magnesium alloy and a method for homogenizing its ingots. Background Technology

[0002] Aluminum-magnesium alloys, with their low density, high specific strength, excellent corrosion resistance, and good formability, have broad application prospects in high-end manufacturing fields such as aerospace, rail transportation, precision instruments, and automotive lightweighting. However, as high-end equipment continues to demand lighter, higher-strength, more stable microstructures, and higher service reliability for structural components, conventional aluminum-magnesium alloys generally suffer from defects such as inhomogeneous microstructure, easy formation of continuous brittle phases at grain boundaries, coarse precipitates, and large fluctuations in mechanical properties, making it difficult to meet the long-term stable service requirements under harsh operating conditions.

[0003] After aluminum-magnesium alloys are smelted and cast, the ingots are prone to metallurgical defects such as compositional segregation, coarse grains, and the agglomeration and precipitation of non-equilibrium brittle phases. If the homogenization heat treatment process parameters are not properly matched, these defects will be further amplified, leading to deterioration in the alloy's subsequent plastic processing performance, poor stability of the finished product's mechanical properties, and insufficient fatigue resistance. Furthermore, traditional aluminum-magnesium alloys lack precise control over the proportions of trace impurity elements such as Si, Fe, and Cu, only generally limiting the total impurity content. Imbalances in the proportions of impurity elements can easily induce the precipitation of brittle compounds, disrupting the matrix continuity and reducing the alloy's purity and structural stability. In addition, traditional homogenization processes often employ a single heat treatment regime with fixed parameters, without differentiated design for the heat transfer characteristics of ingots of different sizes. Thin ingots are prone to grain overheating and high production energy consumption, while thick ingots suffer from insufficient solute diffusion in the core, poor structural uniformity, and significant internal and external property gradients, severely restricting the overall performance of the finished alloy and the consistency of mass production.

[0004] Currently, the industry mainly modifies aluminum-magnesium alloys by adding light rare earth elements such as lanthanum and cerium, utilizing the grain refinement and impurity removal effects of rare earths to improve the alloy's microstructure and properties. However, existing light rare earth modification systems have significant technical shortcomings: First, the bonding stability between lanthanum and cerium light rare earth elements and the aluminum-magnesium matrix is ​​relatively weak, and under high-temperature service conditions, coarsening of precipitates and loosening of the microstructure are prone to occur, resulting in a significant decrease in the alloy's high-temperature mechanical properties and thermal stability, making it unsuitable for harsh operating conditions such as high temperatures and alternating loads; Second, existing rare earth aluminum-magnesium alloys lack a proportional constraint mechanism for Si, Fe, and Cu impurity elements, and the disordered enrichment of impurities easily forms needle-like and blocky brittle intermetallic compounds, which rupture the alloy matrix and significantly reduce the alloy's plasticity and fracture toughness; Third, traditional heat treatment process parameters are fixed and not adapted to differences in ingot size and alloy composition, making thin ingots prone to overheating and thick ingots lacking in thorough homogenization, resulting in poor process adaptability and difficulty in ensuring the performance consistency of batch products. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a method for homogenizing lutetium-containing aluminum-magnesium alloys and their ingots. To achieve the above objectives, the present invention provides the following technical solution: A lutetium-modified aluminum-magnesium alloy has the following specific composition: Mg: 2.0-6.0%, Mn: 0.10-1.00%, Cr: 0.05-0.35%, Lu: 0.1-1.5%, Si: 0.05-0.20%, Fe: 0.05-0.30%, Cu: 0.01-0.10%, Zn: 0.08-0.20%, Ti: 0.05-0.15%; wherein the mass percentage of a single impurity element is ≤0.05%, the total mass percentage of impurities is ≤0.12%, and the balance is Al.

[0006] Furthermore, the mass percentage of Si in the alloy is less than that of Fe, and the total mass percentage of Si, Fe, and Cu is 0.15–0.45%. This compositional constraint can precisely suppress the disordered enrichment of Si, Fe, and Cu impurities to form needle-like and blocky brittle intermetallic compounds, effectively eliminate matrix fracture defects induced by impurities, and significantly improve the uniformity and purity of the as-cast microstructure of the alloy, thus ensuring the alloy's plasticity, toughness, and corrosion resistance from a compositional perspective.

[0007] The specific mechanisms of element action in this scheme are as follows: Mg element enhances the strength and plasticity of the alloy matrix through solid solution strengthening, adapting to the load-bearing requirements of lightweight structural components; Mn element refines the as-cast grains, inhibits high-temperature recrystallization, and improves the alloy's cold and hot working properties; Cr element synergistically refines the grains, improving the alloy's thermal stability and corrosion resistance; trace amounts of Lu rare earth elements are the core modifying components, which can efficiently purify grain boundaries, refine precipitated phases, and inhibit the continuous precipitation of brittle phases at grain boundaries, significantly improving the alloy's high-temperature structural stability, low-temperature toughness, and fatigue resistance; Ti element refines the cast grains, reducing casting defects such as porosity and segregation; Zn element assists in improving the alloy's strength and corrosion resistance; Si, Fe, and Cu, through the exclusive proportion constraints of this invention, avoid harmful defects and ensure the alloy's comprehensive service performance.

[0008] Furthermore, in this scheme, the continuous network of brittle Mg2Al3 phases at the alloy grain boundaries is significantly reduced, alleviating or eliminating the brittle defects at grain boundaries in traditional aluminum-magnesium alloys. Ultrafine Al3Lu reinforcing phase particles with a particle size of 30–1500 nm are formed within the alloy matrix, and these Al3Lu reinforcing phases are uniformly dispersed throughout the alloy matrix. In this scheme, the dispersed and refined Al3Lu reinforcing phases achieve efficient dispersion strengthening and refine the matrix grains. While ensuring the alloy's excellent plasticity and forming and processing properties, it significantly improves the alloy's strength, hardness, low-temperature toughness, corrosion resistance, and fatigue stability, fully supporting the performance and microstructure protection scope corresponding to the claims.

[0009] A homogenization treatment method for lutetium-aluminum-magnesium alloy ingots is proposed. To adapt to the proprietary differentiated process for lutetium-aluminum-magnesium alloys, alloy raw materials with qualified proportions are smelted, refined, allowed to stand for impurity removal, and semi-continuously cast to prepare alloy flat ingots. After trimming, a homogenization treatment mode is selected according to the thickness difference of the flat ingots. Among them, thin-specification ingots with thickness H≤100mm adopt a platform-type homogenization process, while thick-specification ingots with thickness H>100mm adopt a two-stage step-type homogenization process. This method completely solves the technical drawback of traditional single solidification process, which cannot take into account the homogenization effect of thick and thin ingots, and achieves controllable uniformity of microstructure and consistent performance of ingots of all specifications.

[0010] Furthermore, the length L of the flat ingot is 300–12500 mm, the width W is 150–2700 mm, and the thickness H is 20–700 mm; the dimensional ratios satisfy L≥W≥H, 1.0≤L / W≤8.0, and 1.5≤W / H≤7.0. These dimensional and proportional constraints serve as the basis for adapting to differentiated heat treatment processes, ensuring uniform temperature fields and stable heat conduction during heat treatment of ingots of different specifications. This avoids defects such as uneven microstructure caused by localized overheating and insufficient heat preservation, ensuring that all compliant ingots achieve the homogeneous effect and microstructure properties defined in the claims.

[0011] Furthermore, for the platform-type homogenization process of thin ingots with H≤100mm, the basic process parameters are strictly limited as follows: homogenization temperature 470~500℃, holding time 10~18h; after holding, slow cooling in the furnace to 270℃ or below, followed by natural air cooling after removal from the furnace. Gradual slow cooling in the furnace can effectively release residual stress inside the ingot, avoid stress concentration and structural defects caused by rapid cooling, and ensure the alloy's formability and service stability.

[0012] Temperature parameters are strictly controlled according to the magnesium content zoning rules: when the Mg mass content is 2.0-3.5%, the homogenization temperature is controlled at 480-500℃ to ensure sufficient solid solution diffusion of the low-magnesium alloy solute and completely eliminate as-cast segregation defects; when the Mg mass content is 3.5-6.0%, the homogenization temperature is controlled at 470-490℃ to avoid the problems of high-magnesium alloy overheating and abnormal grain growth, and to accurately match the solid solution temperature window of the high-magnesium alloy.

[0013] The holding time is strictly controlled according to the matching rules of the furnace charge: when the furnace charge is ≤5 tons, the holding time is 10-16 hours to match the rapid homogenization characteristics of small furnace charge; when the furnace charge is >5 tons, the holding time is 12-18 hours to compensate for the heat transfer lag problem of large furnace charge and ensure that all ingots have uniform homogenization effect and meet the performance standards.

[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention constructs a high-precision and controllable lutetium-containing aluminum-magnesium alloy composition system, uses lutetium rare earth element modification, and establishes a ternary impurity ratio constraint mechanism of Si, Fe and Cu, which limits the mass ratio of Si to be less than that of Fe and the total content of the three to be controllable. This suppresses the generation of brittle compounds from the source of composition, realizes the purification of matrix grain boundaries and the refinement of microstructure, and breaks through the technical bottleneck of poor thermal stability and many impurity defects in traditional light rare earth modified aluminum-magnesium alloys.

[0015] (2) The present invention realizes the directional controllable regulation of the microstructure of the alloy, and achieves an excellent microstructure with a significant reduction in the brittle Mg2Al3 phase of the grain boundary and a dispersed distribution of ultrafine Al3Lu particles. It significantly improves the strength, plasticity, toughness and fatigue resistance of the alloy, and solves the defects of traditional aluminum-magnesium alloys with large grain boundary brittleness and easy cracking under stress.

[0016] (3) This invention constructs a dual-mode differentiated homogenization process system of "platform type + two-stage step type" for ingots of different thicknesses and sizes. It combines the magnesium content range, furnace loading amount and ingot size to quantitatively match heat treatment parameters in multiple dimensions. It establishes a special heat preservation time calculation formula for thick ingots, which effectively solves the technical problems of poor adaptability, incomplete homogenization and poor product performance consistency of traditional single process, and takes into account both high-end product quality and industrial production efficiency. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the homogenization process of the present invention; Figure 2 This is a schematic diagram of the temperature-time curves for the platform-type and two-stage step-type homogenization processes of the present invention; Figure 3 SEM images of the as-cast state: (a) Al-Mg(5154) alloy; (b) Al-Mg(5154) alloy containing 0.3% Lu; Figure 4 SEM (TEM) images after homogenization: (a) Al-Mg(5154) alloy (b) Al-Mg(5154) alloy containing 0.3% Lu (c) Al-Mg(5154) alloy containing 0.3% Lu (TEM); Figure 5 The surface morphology after corrosion is shown in the following figures: (a) Al-Mg(5154) alloy and (b) Al-Mg(5154) alloy containing 0.3% Lu. Figure 6 For as-cast corrosion resistance: (a) polarization (Tafel) curves of Al-Mg-xLu alloy; (b) mass loss (mg / cm2) due to intergranular corrosion of Al-Mg-xLu alloy. Detailed Implementation

[0018] To make the technical solution, technical features, and beneficial effects of the present invention clearer and more complete, the present invention will be described in detail below with reference to the embodiments. All embodiments of the present invention strictly follow the alloy composition constraints, microstructure indicators, ingot size specifications, and differentiated homogenization processes disclosed in the present invention. All parameters fall within the defined range, without deviation or custom adjustments.

[0019] The unified alloy preparation process of this invention is as follows: precise batching control → smelting and refining to remove impurities → melt settling and purification → semi-continuous casting of alloy flat ingots → ingot size trimming → differentiated homogenization heat treatment → gradient slow cooling → furnace air cooling → sampling and testing.

[0020] The general process control standards are as follows: During the ingredient preparation stage, the proportion of each element is strictly controlled to ensure that the mass percentage of a single impurity element is ≤0.05% and the total mass percentage of impurities is ≤0.12%, while also meeting the core constraints of Si<Fe and Si+Fe+Cu=0.15~0.45%. The smelting temperature is controlled at 720-760℃, and after refining, it is allowed to stand for 30-60 minutes to ensure high purity of the melt. After casting, the size of the flat ingot is trimmed to meet the ratio requirements of L≥W≥H, 1.0≤L / W≤8.0, and 1.5≤W / H≤7.0.

[0021] Heat treatment is selected based on the ingot thickness: for H≤100mm, a platform homogenization process is adopted, matched with magnesium content zone temperature control and furnace charge time-based temperature control; for H>100mm, a two-stage step homogenization process is adopted, and the holding time is determined by the size quantification formula, with a total holding time of ≤25h for both stages; in the cooling stage, the furnace is slowly cooled with the furnace at ≤270℃ and ≤280℃ respectively, and then the ingot is air-cooled after being removed from the furnace.

[0022] Example 1 In Example 1, the alloy composition (mass percentage) is as follows: Mg: 2.0%, Mn: 0.10%, Cr: 0.05%, Lu: 0.10%, Si: 0.05%, Fe: 0.12%, Cu: 0.01%, Zn: 0.08%, Ti: 0.05%, with each single impurity element having a mass percentage ≤ 0.05%, the total impurity mass percentage ≤ 0.12%, and the balance being Al; the composition satisfies the condition that the mass percentage of Si < the mass percentage of Fe, and the total mass percentage of Si + Fe + Cu is 0.18%.

[0023] The ingot specifications in this embodiment are as follows: flat ingot length L=1000mm, width W=500mm, thickness H=60mm, thickness H≤100mm, suitable for platform homogenization process, and the ingot size ratio meets the limiting conditions of L≥W≥H, 1.0≤L / W≤8.0, and 1.5≤W / H≤7.0.

[0024] In this embodiment, the homogenization heat treatment process is as follows: the Mg content is in the low magnesium range of 2.0-3.5%, the homogenization temperature is set at 495℃, the furnace charge is 4t, the holding time is 12h, and after the holding time is completed, the furnace is slowly cooled to 268℃, and then the furnace is naturally air-cooled.

[0025] Testing revealed that the alloy obtained in this embodiment has clean grain boundaries and no continuous network of brittle Mg2Al3 phase precipitation; the Al3Lu strengthening phase has uniform size, with a particle size concentrated in the range of 30–500 nm, and is diffusely distributed throughout the matrix without segregation, agglomeration, or coarse precipitation defects. The alloy exhibits low residual stress, excellent formability, and good corrosion resistance.

[0026] Example 2 In Example 2, the alloy composition (mass percentage) is as follows: Mg: 3.0%, Mn: 0.50%, Cr: 0.20%, Lu: 0.80%, Si: 0.10%, Fe: 0.18%, Cu: 0.04%, Zn: 0.12%, Ti: 0.10%, with the balance being Al. The composition satisfies Si < Fe, and the total mass percentage of Si + Fe + Cu is 0.32%. The impurity content meets the specifications.

[0027] The ingot specifications in this embodiment are as follows: flat ingot length L=2000mm, width W=800mm, thickness H=90mm, which belongs to the thin-gauge ingot with H≤100mm, and is suitable for the platform-type homogenization process.

[0028] In this embodiment, the homogenization heat treatment process is as follows: the Mg content is in the low magnesium range, the homogenization temperature is set to 488℃; the furnace charge is 7t, the holding time is 16h; after the holding time is completed, the furnace is slowly cooled to 262℃, and then the furnace is air cooled.

[0029] Testing revealed that the alloy in Example 2 exhibits excellent overall microstructure uniformity, with uniformly dispersed Al3Lu reinforcing phase of appropriate size. It is free from overheating, underheating, and microstructural defects, demonstrating stable mechanical properties and balanced overall performance, making it suitable for industrial mass production.

[0030] Example 3: In this embodiment 3, the alloy composition (mass percentage) is as follows: Mg: 6.0%, Mn: 1.00%, Cr: 0.35%, Lu: 1.50%, Si: 0.18%, Fe: 0.28%, Cu: 0.06%, Zn: 0.18%, Ti: 0.14%, with the balance being Al; the composition satisfies Si < Fe, and the total mass percentage of Si + Fe + Cu is 0.42%.

[0031] In this embodiment, the ingot specifications are as follows: the thickness of the flat ingot is H=100mm, which is the critical thickness for thin specifications; the length is L=1500mm and the width is W=700mm; the size ratio fully meets the specified conditions.

[0032] In this embodiment, the homogenization heat treatment process is as follows: the Mg content is in the high magnesium range of 3.5-6.0%, the homogenization temperature is set at 472℃, the furnace charge is 6t, the holding time is 17h, after the holding time is completed, the furnace is slowly cooled to 260℃, and then the furnace is air cooled.

[0033] After testing, it was found that under the extreme conditions of high magnesium and high lutetium ratio, the alloy grain boundaries in Example 3 remained clean and no continuous network brittle phase was generated; the Al3Lu refinement and strengthening effect was significant, with no coarse grains or overheating defects, which completely solved the problem of poor microstructure stability of traditional high magnesium alloys.

[0034] Example 4: In Example 4, the alloy composition (mass percentage) is as follows: Mg: 4.0%, Mn: 0.60%, Cr: 0.25%, Lu: 0.50%, Si: 0.11%, Fe: 0.20%, Cu: 0.03%, Zn: 0.10%, Ti: 0.09%, with the balance being Al; the composition satisfies Si < Fe, and the total mass percentage of Si + Fe + Cu is 0.34%.

[0035] The ingot specifications in this embodiment are as follows: flat ingot thickness H=150mm, width W=800mm, length L=3000mm, thickness H>100mm, suitable for two-stage step homogenization process, and the size ratio is compliant.

[0036] The homogenization heat treatment process in this embodiment adopts a two-stage step process. The parameters are calculated according to the size quantification formula of this invention. The first stage is held at 485℃ for 9 hours, the second stage is held at 450℃ for 5 hours, and the total holding time is 14 hours, which meets the requirement of a total time of ≤25 hours. After the holding is completed, the furnace is slowly cooled to 275℃ and then air-cooled after being removed from the furnace. The process parameters are fully compliant.

[0037] After testing, the internal and external structures of Example 4 were found to be uniform and consistent, with no difference in internal and external performance gradients. The solute diffusion in the core was sufficient, and there were no metallurgical defects such as component segregation or porosity. The flaw detection met the standards.

[0038] Example 5: In Example 5, the alloy composition (mass percentage) is as follows: Mg: 5.0%, Mn: 0.80%, Cr: 0.30%, Lu: 1.20%, Si: 0.13%, Fe: 0.24%, Cu: 0.05%, Zn: 0.15%, Ti: 0.12%, with the balance being Al. The composition satisfies the condition that Si < Fe, and the total mass percentage of Si + Fe + Cu is 0.42%, which meets the proportioning requirements.

[0039] The specifications of the ingot in this embodiment are as follows: thickness H=700mm, width W=2500mm, and length L=12000mm.

[0040] The homogenization heat treatment process in this embodiment adopts a two-stage step process. According to the quantitative calculation of the exclusive formula, the first stage is held at 485℃ for 13 hours, the second stage is held at 450℃ for 8 hours, and the total holding time is 21 hours, which is less than the upper limit threshold of 25 hours. After the holding is completed, the furnace is slowly cooled to 278℃ and then air-cooled after being removed from the furnace. The process parameters are fully compliant.

[0041] After testing, the microstructure in Example 6 was found to be uniform and dense, without any looseness, segregation, or porosity defects. It exhibited excellent low-temperature toughness and corrosion resistance, and there was no problem with core performance degradation.

[0042] Example 6: In Example 6, the alloy composition (mass percentage) is as follows: Mg: 4.5%, Mn: 0.7%, Cr: 0.15%, Lu: 0.25%, Si: 0.12%, Fe: 0.22%, Cu: 0.05%, Ti: 0.08%, Zn: 0.12%, with each single impurity element ≤0.05%, the total impurity content ≤0.12%, and the balance being Al. The composition satisfies the core constraint conditions of Si < Fe and Si + Fe + Cu = 0.39%.

[0043] In this embodiment, the ingot specifications are as follows: flat ingot thickness H=80mm, H≤100mm, suitable for platform-type homogenization process, and the ingot size ratio requirements are standardized.

[0044] In this embodiment, the homogenization heat treatment process is as follows: the Mg content is 4.5%, which is in the high magnesium range; the homogenization temperature is 475℃; the furnace charge is 8t; the holding time is 14h; the furnace is slowly cooled to 265℃ and then air-cooled after being taken out of the furnace. The process parameters are completely in line with the requirements.

[0045] Testing revealed that the alloy in Example 6 exhibited clean grain boundaries free of continuous network-like Al3Lu brittle phases, with fine and dispersed Al3Lu reinforcing phases free of agglomeration and coarse defects, resulting in excellent microstructure uniformity. The alloy exhibits low residual stress, good formability and corrosion resistance, and exhibits no cracking during plastic processing, thus meeting the service requirements of high-end lightweight components.

[0046] Example 7: In Example 7, the alloy composition (mass percentage) is as follows: Mg: 5.0%, Mn: 0.7%, Cr: 0.15%, Lu: 0.30%, Si: 0.12%, Fe: 0.22%, Cu: 0.05%, Ti: 0.08%, Zn: 0.12%. The impurity content is compliant, and the balance is Al. The composition meets the constraints of Si < Fe and Si + Fe + Cu = 0.39%.

[0047] The ingot specifications in this embodiment are as follows: flat ingot thickness H=420mm, width W=1800mm, H>100mm, suitable for two-stage step homogenization process, and the size ratio meets the requirements.

[0048] The homogenization heat treatment process in this embodiment is as follows: the first-stage heat preservation temperature is 480℃ and the heat preservation time is 12 hours; the second-stage heat preservation temperature is 455℃ and the heat preservation time is 7 hours; the heat preservation time is 19 hours; the furnace is slowly cooled to below 280℃ and then air-cooled. All process parameters are compliant.

[0049] After testing, the ingot in Example 7 showed a uniform overall microstructure with no compositional segregation or internal / external microstructure gradient, and the flaw detection level reached Class I. The alloy exhibits excellent corrosion resistance and low-temperature toughness, with minimal performance degradation and strong deformation capacity in the thick core, making it suitable for the demanding service conditions of large, high-end structural components.

[0050] Comparative example (conventional 5154 aluminum-magnesium alloy, lutetium-free, traditional single-stage homogenization process) This comparative example uses commercially available conventional 5154 aluminum-magnesium alloy without the addition of lutetium rare earth elements. It is not subject to the ternary impurity ratio constraints of this invention and employs a traditional single-stage isothermal homogenization process as a reference for the technical solution of this invention. Testing revealed that the conventional 5154 alloy exhibits continuous network-like brittle Mg2Al3 phases at the grain boundaries, disrupting the matrix continuity and exhibiting significant grain boundary brittleness. The alloy also exhibits poor corrosion resistance, with a salt spray corrosion rate significantly higher than that of the alloys in the embodiments of this invention. In the thick ingot core, insufficient solute diffusion and severe microstructure segregation lead to a significant decrease in core toughness, making it prone to cracking and failure under stress. Overall, its service performance and stability are far inferior to the lutetium-containing aluminum-magnesium alloy of this invention.

[0051] Based on Example 7 and the comparative example, the mechanism and effect of this solution are further demonstrated.

[0052] like Figure 2 As shown, this invention employs a platform-type isothermal process curve for thin ingots with H≤100mm. The isothermal platform temperature and holding time are precisely locked according to the magnesium content range and furnace charge. This ensures sufficient diffusion of solute atoms and eliminates as-cast segregation while avoiding grain overheating and microstructure deterioration caused by prolonged high temperatures in thin ingots. For medium-thick and ultra-thick ingots with H>100mm, a two-stage step-type temperature-time curve is used. This involves segmented temperature control through a "high-temperature rapid diffusion section + low-temperature stabilization and refinement section." The initial high-temperature section rapidly activates the solute diffusion dynamics in the core of the thick ingot, completely eliminating core porosity, compositional segregation, and as-cast dendrite defects. The subsequent low-temperature isothermal section stabilizes the grain structure and inhibits abnormal grain growth during long-term heat treatment. This resolves the technical contradiction of traditional single-stage processes failing to simultaneously achieve "complete homogenization" and "structure preservation," providing core process support for the uniformity of microstructure and consistent performance of all ingot sizes in this invention.

[0053] like Figure 3As shown, in the as-cast microstructure of conventional aluminum-magnesium alloys without Lu, a large number of coarse dendrites, continuous network grain boundary precipitates, and obvious compositional segregation regions can be clearly observed. Impurity elements are disorderly enriched, grain boundary outlines are blurred, and defects are dense, which are the original defects of traditional alloys in the as-cast state, resulting in high brittleness and large performance fluctuations. However, the as-cast SEM morphology of the Lu-modified alloy of this invention shows that, relying on the heterogeneous nucleation, grain boundary adsorption, and impurity purification mechanism of lutetium, the as-cast dendrite structure of the alloy is significantly broken down, the grains are significantly refined, the grain boundary outlines are clear and regular, and there is no aggregation of coarse brittle phases. Combined with the ternary impurity ratio constraint of Si < Fe and Si + Fe + Cu limited by this invention, the precipitation of brittle impurity compounds is suppressed from the solidification source, which greatly improves the purity of the as-cast microstructure and lays the compositional and structural foundation for the high-quality microstructure after subsequent homogenization heat treatment.

[0054] like Figure 4 As shown, after homogenization treatment, the comparative alloy without Lu still exhibits typical defects in its SEM morphology, such as chain-like and network-like brittle Mg2Al3 phases encasing grain boundaries, severely disrupting the matrix continuity. TEM characterization reveals that its precipitated phases are large in size, randomly distributed, lack a uniformly dispersed strengthening phase structure, and exhibit extremely poor microstructural stability. In contrast, the Lu-containing alloy of this invention, after differentiated processing, shows a significant reduction in the precipitation of continuous network-like brittle Mg2Al3 phases at grain boundaries in its SEM images. The grain boundaries are straight and clean, and the microstructure is dense and uniform. Fine TEM characterization confirms the formation of a large number of ultrafine spherical Al3Lu strengthening phases with sizes concentrated in the range of 30–1500 nm within the matrix. These strengthening phases are diffusely distributed throughout the matrix, without agglomeration or coarsening. This microstructural characteristic demonstrates that the lutetium modification mechanism of this invention can synergistically work with the dual-mode homogenization process to completely eliminate the brittle grain boundary defects of traditional alloys through sufficient solute diffusion, defect repair, and dispersion strengthening, achieving a controllable and designable microstructure.

[0055] like Figure 5 As shown, conventional alloys without Lu exhibit numerous corrosion pits, intergranular corrosion grooves, and spalling areas on their surface after corrosion. Corrosion propagates rapidly along grain boundaries, resulting in severe corrosion. This is due to the continuous distribution of brittle phases at grain boundaries and the presence of numerous impurity-rich areas, which easily form corrosion galvanic cells, exacerbating intergranular corrosion and localized pitting failure. The Lu-containing alloy of this invention exhibits a smooth and dense surface after corrosion, without large-area corrosion spalling or deep intergranular corrosion grooves, showing only slight, uniform corrosion traces. The mechanism lies in the following: Lutium purifies grain boundaries and eliminates sensitive sites for grain boundary corrosion; the dispersed Al3Lu reinforcing phase effectively hinders the penetration of corrosive media and the propagation of corrosion cracks; and the precise Si / Fe / Cu ratio constraint avoids localized galvanic corrosion induced by impurity enrichment, significantly improving the alloy's resistance to intergranular corrosion and pitting corrosion.

[0056] like Figure 6As shown in the Tafel polarization curves, the alloy containing the Lu content specified in this invention has a more positive self-corrosion potential and a lower corrosion current density. Its electrochemical corrosion thermodynamic and kinetic stability is significantly better than that of the lutetium-free alloy. The intergranular corrosion mass loss data show that the corrosion mass loss of the lutetium-containing alloy within the ratio range of this invention is much lower than that of conventional lutetium-free alloys. Quantitative data prove that the 0.1-1.5% lutetium content range specified in this invention, the synergistic ternary impurity ratio, and the differentiated heat treatment process can stably optimize the electrochemical corrosion characteristics of the alloy, significantly reduce the risk of intergranular corrosion failure, and achieve quantitative improvement and stable controllability of the alloy's corrosion resistance.

[0057] In summary, combining Figures 2-6 With the comparison results of all embodiments and comparative examples covering the components, critical dimensions, and limit specifications of this invention, it can be fully verified that this invention, through precise modification of lutetium-containing components combined with impurity ratio constraints and a dual-mode differentiated heat treatment coupling mechanism, can stably obtain high-quality microstructure and macroscopic properties that are homogeneous, clean, highly stable, and highly corrosion-resistant. It completely breaks through the microstructure defects and performance bottlenecks of traditional aluminum-magnesium alloys and conventional light rare earth modified alloys. The scheme has a clear mechanism, verifiable data, strong universality, and good repeatability, and has outstanding creativity and industrial application value.

[0058] The embodiments of the present invention are given for illustrative and descriptive purposes only, and are not intended to be exhaustive or to limit the invention to the forms disclosed. Many modifications and variations will be apparent to those skilled in the art. The embodiments were chosen and described in order to better illustrate the principles and practical application of the invention, and to enable those skilled in the art to understand the invention and to design various embodiments with various modifications suitable for a particular purpose.

Claims

1. A lutetium-aluminum-magnesium alloy, characterized in that, In terms of mass percentage, it comprises the following components: Mg: 2.0~6.0%, Mn: 0.10~1.00%, Cr: 0.05~0.35%, Lu: 0.1~1.5%, Si: 0.05~0.20%, Fe: 0.05~0.30%, Cu: 0.01~0.10%, Zn: 0.08~0.20%, Ti: 0.05~0.15%, individual impurity elements ≤0.05% and total impurities ≤0.12%, with the balance being Al; and said alloy components satisfy: Si%<Fe%, and Si+Fe+Cu=0.15~0.45%.

2. The lutetium-containing aluminum-magnesium alloy according to claim 1, characterized in that, The microstructure of said lutetium-containing aluminum-magnesium alloy satisfies: the Al3Lu phase is dispersed in the form of fine particles, with a particle diameter of 30 to 1500 nm.

3. A method for homogenizing lutetium-aluminum-magnesium alloy ingots, characterized in that, Said lutetium-containing aluminum-magnesium alloy is smelted and cast into a flat ingot, the thickness of said flat ingot is H, and the following two homogenization treatment processes are adopted according to the thickness H of said flat ingot: When H≤100mm, a platform-type homogenization process is adopted; When H>100mm, a two-stage stepped homogenization process is adopted.

4. The method for homogenizing lutetium-containing aluminum-magnesium alloy ingots according to claim 3, characterized in that, The dimensions of said flat ingot satisfy: length L is 300~12500mm, width W is 150~2700mm, thickness H is 20~700mm; and L≥W≥H, 1.0≤L / W≤8.0, 1.5≤W / H≤7.0 are satisfied.

5. The homogenization treatment method for an ingot of lutetium-containing aluminum-magnesium alloy according to claim 3, characterized in that, When H≤100mm, the specific parameters of said platform-type homogenization process are: homogenization temperature T is 470~500℃, holding time t is 10~18h; after holding, cool with the furnace to ≤270℃, then discharge from the furnace and air cool; wherein, when the Mg content in the alloy is 2.0%~3.5%, said homogenization temperature T is 480~500℃; when the Mg content in the alloy is 3.5%~6.0%, said homogenization temperature T is 470~490℃.

6. The method for homogenizing lutetium-containing aluminum-magnesium alloy ingots according to claim 5, characterized in that, The holding time t of said platform-type homogenization process is determined according to the furnace charging amount: when the furnace charging amount is ≤5 tons, t is 10~16h; when the furnace charging amount is >5 tons, t is 12~18h.

7. The homogenization treatment method for an ingot of lutetium-containing aluminum-magnesium alloy according to claim 3, characterized in that, When H>100mm, the specific parameters of said two-stage stepped homogenization process are: first-stage holding temperature T1 is 485±5℃, first-stage holding time t1 is 8~18h; second-stage holding temperature T2 is 450±5℃, second-stage holding time t2 is 4~12h; total holding time of the two stages is ≤25h; after holding, cool with the furnace to ≤280℃, then discharge from the furnace and air cool.

8. The method for homogenizing lutetium-containing aluminum-magnesium alloy ingots according to claim 7, characterized in that, The first-stage holding time t1 and second-stage holding time t2 of said two-stage stepped homogenization process are calculated and determined by the following formula: t=t0+Δt; Δt=k1(H-100)+k2(W-700); Where t0 is the reference time, t0 is 8h for the first-level process and 4h for the second-level process; k1 is the thickness increment coefficient, 0.0080h / mm for the first-level process and 0.0055h / mm for the second-level process; k2 is the width increment coefficient, k2=0 when W≤700mm; when W>700mm, k2 is 0.0011h / mm for the first-level process and 0.0009h / mm for the second-level process.